A methods engineering study on Vinyl Resources, Inc. - Encinas, Catherine S.; Nepomuceno, Larissa E.; Salazar, Ana Carolina J. (Diliman, Quezon City College of Engineering, 2000)
Vinyl Resources, Inc. is a 100 percent Filipino corporation engaged in the manufacture of refrigerator and freezer gaskets and other polyvinyl chloride compounds. They have two (2) product lines, namely fused gaskets and PVC tubes. After conducting an analysis of their present system, the problem identified was the enumeration of ways on how to counteract the slump in the business. The group offered the alternatives of laying off some workers and of rescheduling the production of the company. The study yielded the following results : The rescheduling process is recommended. This will include the rescheduling of the working hours of the workers and the machines and will result in the minimization of labor and electricity costs which will help the company now that they are experiencing a temporary slump in the business. This will also help maximize the efficiency of the production system. Since is beyond the scope of Methods Engineering, the rescheduling process was not elaborately discussed. If the company wishes to implement the rescheduling process, higher IE courses would be needed. However, a sample model that was developed using IE 142 Techniques was presented. It should be noted that the said model still has to be verified if it is indeed workable.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Vinyl Resources Inc; Machinery industries; Systems analysis